Assigning precipitation to mid‐latitudes fronts on sub‐daily scales in the North Atlantic and European sector: Climatology and trends. (4th September 2018) - Hénin, Riccardo; Ramos, Alexandre M.; Schemm, Sebastian; Gouveia, Célia M.; Liberato, Margarida L. R.
Abstract : Atmospheric fronts are fundamental features of the weather variability in the mid‐latitudes and are frequently associated with high‐impact weather events such as hail, wind gusts or precipitation. A method to link precipitation with synoptic‐scale fronts on sub‐daily timescales is developed based on ERA‐Interim data (1979–2016). A case study, a climatology and a trend analysis are presented and discussed. Spatially, an optimal attribution radius is identified based on a random sampling technique. The method is demonstrated using a past weather event that occurred over western Europe. Annual and seasonal cycles are presented and confirm, in agreement with previous studies, that frontal precipitation accounts for a large fraction of all precipitation (up to 80%) in the mid‐latitudes, especially during autumn and winter. Finally, a negative trend in frontal precipitation is identified, mostly affecting the Gulf Stream region. Cold fronts drive most of the observed trends in this region and the trend pattern suggests a polewards displacement of the zone of enhanced precipitation. Abstract : A method is presented to relate, in time and space, precipitation to mid‐latitudes synoptic‐scale fronts using 6‐hourly ERA‐Interim data, distinguishing warm and cold fronts (a). The method is validated using a case study occurred over the North Atlantic and European sector (b). Annual and seasonal climatological means for precipitation assigned to fronts are analysed (c). A trend analysis for the period 1979–2016 suggests a statistically significant decrease of precipitation south of the Gulf Stream SST zone, mostly driven by cold fronts.